2022
DOI: 10.1155/2022/4496734
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of a Combined Metabolic Strategy in Glioblastoma Multiforme: A Prospective Case Series

Abstract: Background. Glioblastoma multiforme (GBM) may be susceptible to metabolic strategies such as fasting and ketogenic diets, which lower blood glucose and elevate ketones. Combining these two strategies may be an ideal approach for sustaining a potentially therapeutic glucose ketone index (GKI). In this prospective case series, we observed whether a combined metabolic strategy was feasible, safe, and capable of sustaining a GKI <6 in patients with GBM. Methods. We provided recommendations and guidelines to 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Despite these theoretical advantages, supportive interventional evidence in patients with GBM remains limited (25). Only one study has incorporated a combined fasting and ketogenic diet protocol in a rigorous manner (26). This study showed that an intensive, combined KMT program was feasible and safe in patients with GBM.…”
Section: Introductionmentioning
confidence: 92%
“…Despite these theoretical advantages, supportive interventional evidence in patients with GBM remains limited (25). Only one study has incorporated a combined fasting and ketogenic diet protocol in a rigorous manner (26). This study showed that an intensive, combined KMT program was feasible and safe in patients with GBM.…”
Section: Introductionmentioning
confidence: 92%